Internet connectivity disruption in Yemen (Yemen) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Yemen. Data sourced from IODA.
Network Disruption Incident ID: YE-2026-0027. Severity: critical. Confidence: 65%